Pax3-induced expansion enables the genetic correction of dystrophic satellite cells. Issue 1 (December 2015) - Filareto, Antonio; Rinaldi, Fabrizio; Arpke, Robert; Darabi, Radbod; Belanto, Joseph; Toso, Erik; Miller, Auston; Ervasti, James; McIvor, R.; Kyba, Michael; Perlingeiro, Rita
Abstract Background Satellite cells (SCs) are indispensable for muscle regeneration and repair; however, due to low frequency in primary muscle and loss of engraftment potential after ex vivo expansion, their use in cell therapy is currently unfeasible. To date, an alternative to this limitation has been the transplantation of SC-derived myogenic progenitor cells (MPCs), although these do not hold the same attractive properties of stem cells, such as self-renewal and long-term regenerative potential. Methods We develop a method to expand wild-type and dystrophic fresh isolated satellite cells using transient expression of Pax3. This approach can be combined with genetic correction of dystrophic satellite cells and utilized to promote muscle regeneration when transplanted into dystrophic mice. Results Here, we show that SCs from wild-type and dystrophic mice can be expanded in culture through transient expression of Pax3, and these expanded activated SCs can regenerate the muscle. We test this approach in a gene therapy model by correcting dystrophic SCs from a mouse lacking dystrophin using aSleeping Beauty transposon carrying the humanμDYSTROPHIN gene. Transplantation of these expanded corrected cells into immune-deficient, dystrophin-deficient mice generated large numbers of dystrophin-expressing myofibers and improved contractile strength. Importantly, in vitro expanded SCs engrafted the SC compartment and could regenerate muscle after secondary injury. Conclusion These results demonstrate that Pax3 is able to promote the ex vivo expansion of SCs while maintaining their stem cell regenerative properties.